Prevalence of Vibrio cholerae in Coastal Alternative Supplies of Drinking Water and Association with Bacillus-Like Spore Formers - Shishir, Md. Asaduzzaman; Mamun, Md. Al; Mian, Md. Mahmuduzzaman; Ferdous, Umme Tamanna; Akter, Noor Jahan; Suravi, Rajia Sultana; Datta, Suvamoy; Kabir, Md. Ehsanul (Frontiers in Public Health, 2018)
The scarcity of hygienic drinking water is a normal phenomenon in the coastal areas of Bangladesh due to the high salinity of ground water. The inhabitants of this locality, therefore, live on alternative supplies of water including rain-fed pond water, rainwater, etc, with persistent complex microbial interactions therein, often contaminated with life-threatening pathogens. Hence, this study was aimed at analyzing the prevalence of Vibrio cholerae (Vc) in the alternative drinking waters of Mathbaria, a coastal sub-district neighboring the Bay of Bengal, the efficacy of Pond sand filter (PSF) and the co-association among Bacillus like Spore formers (Sf) and V. cholerae. V. cholerae presumably entrapped into the membrane filter was enriched in APW medium and was isolated on selective TCBS and TTGA media. They were finally identified by Immuno-chromatographic one step rapid test and serology test. A total of 26% Vc positive samples were obtained out of 100 (Ponds -48, Household- 29, PSFs- 23) where 13% cases were pathogenic (Vc O1) and 13% were non-pathogenic (Vc non- O1/ non- O139). The distribution of Vc as observed was 33%, 26% and 13.8% in waters derived from pond surface, PSF and household reservoirs respectively and for pathogenic type, it was 62.5%, 50% and nil respectively. Though none of the samples was identified with pathogenic Vc O139, the statistics represents a significant and augmentative risk of cholera outbreak in the focused area. The antibiotic sensitivity pattern in this study resembled the trend observed during last few years for Vc. The pond sand filter demonstrated its inability to remove V. cholerae from any of the samples and in addition, the filter itself was evidenced to be the source of pathogens and spores in further contamination and transmission. The development of biofilm in the PSF could be hypothesized as the reservoir in contaminating pathogen free water samples. From the test of homogeneity, the risk levels of alternative water sources were estimated equal regarding V. cholerae. Simultaneously, it was determined statistically that the prevalence of Vc, by no means, is influenced by Bacillus like spore-formers be it for pond surface, household or pond sand filter derived water.